1792 Laws Passed in the Territory of the United States North-West of the River Ohio, at 20, Burglary - (:unkn) unknown (My University, 1788)
Prohibited the carrying of any "dangerous weapon" that indicates a violent intention while committing a burglary. Punishable by imprisonment for up to 40 years.
Keywords: CARRY - INTENT TO COMMIT CRIME